Diverse Clinical Presentations of C3 Dominant Glomerulonephritis - Hanna, Ramy M.; Hou, Jean; Hasnain, Huma; Arman, Farid; Selamet, Umut; Wilson, James; Olanrewaju, Samuel; Zuckerman, Jonathan E.; Barsoum, Marina; Yabu, Julie M.; Kurtz, Ira (Frontiers in Medicine, 2020)
C3 dominant immunofluorescence staining is present in a subset of patients with idiopathic immune complex membranoproliferative glomerulonephritis (iMPGN). It is increasingly recognized that iMPGN may be complement driven, as are cases of “typical” C3 glomerulopathy (C3G). In both iMPGN and C3G, a frequent membranoproliferative pattern of glomerular injury may indicate common pathogenic mechanisms via complement activation and endothelial cell damage. Dysregulation of the alternative complement pathway and mutations in certain regulatory factors are highly implicated in C3 glomerulopathy (which encompasses C3 glomerulonephritis, dense deposit disease, and cases of C3 dominant MPGN). We report three cases that demonstrate that an initial biopsy diagnosis of iMPGN does not exclude complement alterations similar to the ones observed in patients with a diagnosis of C3G. The first patient is a 39-year-old woman with iMPGN and C3 dominant staining, with persistently low C3 levels throughout her course. The second case is a 22-year-old woman with elevated anti-factor H antibodies and C3 dominant iMPGN findings on biopsy. The third case is a 25-year-old woman with C3 dominant iMPGN, dense deposit disease, and a crescentic glomerulonephritis on biopsy. We present the varied phenotypic variations of C3 dominant MPGN and review clinical course, complement profiles, genetic testing, treatment course, and peri-transplantation plans. Testing for complement involvement in iMPGN is important given emerging treatment options and transplant planning.